How successful are women all around champions on apparatus events at OG 1952-2016 - Pajek, M. B. (International Scientific Congress Slovenian Gymnastics Federation, 2018)
Active female participation at Olympic Games (OG) has started in Amsterdam 1928. Only team awards were given until 1952 in Helsinki, where individual awards for all around and apparatus finals were given for the first time. Ex Soviet union gymnast Maria Gorochovskia was the first all-around champion but she did not manage to win any of the four apparatus (vault, uneven bars, balance beam, floor). During seventeen subsequent OG only five winners of all around championship managed to win one or more champion tittles at single apparatuses: Larisa Latynina (ex - Soviet Union) in 1956 (vault) and 1960 (floor), Vera Èaslavska (ex - Czechoslovakia) in 1964 (vault, balance beam) and 1968 (vault, uneven bars, floor), Nadia Comaneci (Romania) in 1796 (uneven bars, balance beam), Lilia Podkopayeva (Ukraine) in 1996 (floor) and Simone Billes (USA) in 2016 (vault, floor). This analysis has shown that all around champions manage to get at least one medal on single apparatuses. The only exception was in 2012 when the all-around champion Douglas Gabrielle (USA) didn`t get any medals on individual apparatus finals. With only four disciplines of all around championship and with three of them directly correlated to acrobatics performance and due to low number of apparatus specialists, it is very much probable that also in the future all-around champions will excel further at single apparatus finals.